High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

A case study on indoor air quality assessments and health risk implications across diverse university environments - Jheng Fong Tsai; Yu-Hsiang Cheng; Zong-Rong Chen; Chi-Chi Lin (Atmospheric Pollution Research, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

A steroid-rich fraction from parasitic climber Cocculus hirsutus (L.) W.Theob inhibits coronavirus disease and neutrophilic inflammation - Vidya Febrasca Tenderly; Thiyagarajan Raviraj; Yen Chi Loo; Olha Mykhailenko; Marcela Safratova; Stefan Kosturko; Mahendra Jadhao; Yu-Li Chen; Tsong-Long Hwang; Fang-Rong Chang; Michal Korinek (Phytochemistry Letters, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

The attenuation of disinfection by-products from the chlorination of secondary effluent organic matter in the presence of bromide under UV365 irradiation: photodegradation mechanism and safety assessment - Kailu Chi; Xiaoyan Y. Ma; Yali An; Jiahui Kho; Jiangyong Hu; Rong Chen; Xiaochang C. Wang (Chemical Engineering Journal, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Efficient adsorption and separation of glyphosate in aqueous solution by amino-functionalized Poly(glycidyl methacrylate) - Qiyu Meng; Yupei Wang; Meng Rong; Huifang Xing; Ru-An Chi; Congmei Chen; Huizhou Liu; Liangrong Yang (Chemical Engineering Journal, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Biochar modulates intracellular electron transfer for nitrate reduction in denitrifying anaerobic methane oxidizing archaea - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Multi-Segment Foot Kinematics during Gait in Adults with Asymptomatic and Symptomatic Flatfoot - Wei-Chi Tsai; Zong-Rong Chen; Jui-Tse Hsu; Chen-Yi Song (Journal of Medical and Biological Engineering, 2024)
Purpose To investigate the differences in foot kinematics during gait between adults with asymptomatic and symptomatic flatfoot. Methods The study included 10 participants (six males and four females, aged 25.7 ± 6.5 years) with symptomatic flatfoot and 10 participants (eight males and two females, aged 21.2 ± 1.0 years) with asymptomatic flatfoot. Multi-segment foot kinematics were captured during barefoot gait analysis using a 3D software. Angles were calculated for the calcaneus with respect to the shank (Sha-Cal), the midfoot with respect to the calcaneus (Cal-Mid), and the metatarsus with respect to the midfoot (Mid-Met) during the stance phase. Results Some differences were noted between medium-to-large effect sizes. The symptomatic group had a decreased Mid-Met dorsiflexion angle at the initial contact to 50% of the stance phase compared with the asymptomatic group. The symptomatic group also showed decreased Mid-Met abduction at initial contact, larger Sha-Cal eversion angles at 10% of the stance phase, and larger Cal-Mid eversion angles at 50% and 70% of the stance phase compared to the asymptomatic group. The symptomatic group also had a larger peak Sha-Cal eversion angle than the asymptomatic group. Conclusion Adults with symptomatic flatfoot exhibit significant differences in foot kinematics towards decreased forefoot dorsiflexion at initial contact to mid-stance, decreased forefoot abduction at initial contact, and increased rearfoot eversion during the stance phase compared with those with asymptomatic flatfoot during gait. Pain may impair intersegmental motion.

Recovery and genetic characterization of clinically-relevant ST2 carbapenem-resistant Acinetobacter baumannii isolates from untreated hospital sewage in Zhejiang Province, China - Danxia Gu; Yuchen Wu; Kaichao Chen; Yanyan Zhang; Xiaoyang Ju; Zelin Yan; Miaomiao Xie; Edward Wai Chi Chan; Sheng Chen; Zhi Ruan; Rong Zhang; Jun Zhang (Science of The Total Environment, 2024)

Efficient perchlorate reduction in microaerobic environment facilitated by partner methane oxidizers - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Journal of Hazardous Materials, 2024)

Photo-driven dynamic hydrogel modulates bone marrow mesenchymal stem cells behavior for enhanced cartilage regeneration - Wenjie Zhang; Wenliang Xue; Zhaoli Jia; Rong Yang; Penghui Wang; Yi Hu; Xiaoyan Tan; Qiang Chen; Bo Chi (Chemical Engineering Journal, 2024)

Installation Disturbance of Helical Anchor in Dense Sand and the Effect on Uplift Capacity Based on Discrete Element Method - Rong Chen; Hu Liu; Dongxue Hao; Zhaoguo Liu; Chi Yuan (Journal of Marine Science and Engineering, 2024)
Helical anchors have been extensively employed as foundation systems for carrying tension loads due to their installation efficiency and large uplift capacity. However, the installation influences of helical anchors are still not well understood, especially for multi-helical anchors. The matrix discrete element method was used to model the process of helical anchor penetration and pull-out in dense sand to investigate the effects of the anchor geometry and advancement ratio (AR, the relative vertical movement per rotation) on soil disturbance, the particle flow mechanism, and the uplift capacity. For shallow helical anchors, the overall disturbance zone is the shape of an inverted cone after installation, while for deep helical anchors, it is funnel-shaped. The advancement ratio has significant effects on the soil particle movement and uplift capacity of helical anchors. The soil particle flow mechanism around helical plates has been identified for single-helix anchors at various advancement ratios, and for double-helix anchors, the influence of the top plate on particle movement during installation was investigated. The uplift capacities of both single- and double-helix anchors increase with the decrease in the AR (AR = 0.5~1), and the influence decreases with the anchor embedment ratio. The efficiency of double-helix anchors induced by installation is close to 1 at pitch-matched installation (AR = 1), indicating that the impact of the top plate during installation is minimal in this case.

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Investigation of lysing excess sludge slurry using hydrolase secreting thermophilic bacterial communities - Baoyan Chi; Ying Huang; Zhenfeng Xiong; Jiali Tan; Weidong Zhou; Zhuo Yang; Kemei Zhou; Xinxin Duan; Ao Chen; Rong Zha; Keting Gui (Journal of Environmental Management, 2024)

Sludge lysis by thermophilic bacteria community enhances nutrient removal, sludge reduction, and modulates microbial community in anaerobic-anoxic-oxic process - Baoyan Chi; Ying Huang; Zhenfeng Xiong; Jiali Tan; Weidong Zhou; Zhuo Yang; Kemei Zhou; Xinxin Duan; Ao Chen; Rong Zha; Keting Gui (Journal of Water Process Engineering, 2023)

Facile spinning of tough and conductive eutectogel fibers via Li+-induced dense hydrogen-bond networks - Lingtao Fang; Chi Zhang; Wenjiao Ge; Mingming Rong; Fan Chen; Zijian Chen; Xiaohui Wang; Zijian Zheng; Qiyao Huang (Chemical Engineering Journal, 2023)

Experimental Investigation on Particle Breakage Behavior of Marine Silica Sand under High-Stress Triaxial Shear - Rong Chen; Tong Zhao; Zhiyong Wu; Dongxue Hao; Nan Xue; Chi Yuan (Journal of Marine Science and Engineering, 2023)
There is often obvious particle breakage for silica sand under high-stress, which will lead to the bearing capacity reduction and excessive settlement of the foundation. This paper focuses on the particle breakage characteristics of marine silica sand from the East China Sea under high-stress conditions. A series of conventional triaxial tests for silica sand, including consolidated drained (CD) and consolidated undrained (CU) shear tests, were conducted under the confining pressures in the range of 2–8 MPa to investigate the breakage rule during the shearing process. The developments of particle breakage index Br with axial strain ε1 and volumetric strain εv present hyperbolic and linear trends, respectively. A hyperbolic model was adopted to describe the relationship of Br and ε1 and the corresponding model parameters were obtained. The particle breakage index also has a good correlation with the input work per unit volume under various average stresses, regardless of the stress history. Furthermore, the relationship between the fractal dimension and the particle breakage was studied based on the particle size distribution curve. It is concluded that the fractal dimension increases in an up–convex hyperbolic trend with the increase of particle breakage index. The dividing radius for whether the silica sand particles exhibit the fractal features is determined as approximately 0.4 mm. This is anticipated to provide reference and supplementary test data for analyzing sand constitutive models/environments regarding particle crushing.

In vitro antioxidant, antiglycation, α-glucosidase and α-amylase inhibitory activities of extracts and solvent fractions of Elaeocarpus serratus L. - Zakhele Mphatsi Dlamini; Chiy-Rong Chen; Bongani Sicelo Dlamini; Chi-I Chang (Biocatalysis and Agricultural Biotechnology, 2023)

Numerical Investigation of Uplift Failure Mode and Capacity Estimation for Deep Helical Anchors in Sand - Chi Yuan; Dongxue Hao; Rong Chen; Ning Zhang (Journal of Marine Science and Engineering, 2023)
The uplift capacity of helical anchors is generally taken as the control condition for design in different applications, including transmission tower foundations and offshore structures. However, it is difficult to identify the failure surface for a deep helical anchor, which may result in an incorrect assessment of uplift capability. This research proposes a new unified method to estimate the uplift capacity of deep single-helix and multi-helix anchors based on the investigation of failure mechanisms. The deep failure mode was identified by FEM analysis using a modified Mohr–Coulomb model considering the strain softening of sand, along with the coupled Eulerian–Lagrangian technique. Thereby, a simplified rupture surface is proposed, and the equations estimating the uplift capacity are presented by the limit equilibrium method. Two important factors—the lateral earth pressure coefficient and the average internal friction angle included in the equations—are discussed and determined. The comparisons with centrifugal tests verify the reasonability of the proposed method.

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Far-field Coupling and Interactions in Multiple Geospheres After the Tonga Volcano Eruptions - Chieh-Hung Chen; Yang-Yi Sun; Xuemin Zhang; Fei Wang; Kai Lin; Yongxin Gao; Chi-Chia Tang; Jun Lyu; Rong Huang; Qian Huang (Surveys in Geophysics, 2023)

Insights into the α-amylase and α-glucosidase inhibition mechanism of 4-(4-hydroxyphenyl)-but-3-en-2-one from Scutellaria barbata D. Don: enzymatic kinetics, fluorescence spectroscopy and computational simulation - Bongani S. Dlamini; Chiy-Rong Chen; Wen-Ling Shih; Yu-Kuo Chen; Jue-Liang Hsu; Chi-I Chang (Medicinal Chemistry Research, 2022)

Experimental Investigation on Behavior of Single-Helix Anchor in Sand Subjected to Uplift Cyclic Loading - Dongxue Hao; Jianyi Che; Rong Chen; Xin Zhang; Chi Yuan; Xichao Chen (Journal of Marine Science and Engineering, 2022)
Helical anchors have been widely used in geotechnical engineering due to their large uplift resistance. However, the current knowledge of the cyclic performance of helical anchors is still insufficient. Consequently, a series of small-scale model tests are carried out in sand to investigate the influences of embedment ratio, sand compactness and the cyclic parameters on the monotonic, cyclic and post-cyclic performance of single-helix anchors. The tests results indicate that the single-helix anchors with optimal embedment ratio still exhibit a relatively high uplift capacity after suffering cyclic load. The cyclic frequency has the greatest influence on the accumulated displacement, and the influence of amplitude is relatively greater than that of the mean cyclic load. The anchors in dense sand exhibit better performance to resist pullout than those in medium–dense sand under the same cyclic parameter ratios. Moreover, the correlation of post-cyclic uplift capacity and displacement after cyclic loading as well as the possible influence of the upward displacement on the sand flow above the helix are discussed.

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Development and characterization of 32 SNP markers for the northern snakehead (Channa argus) using high resolution melting (HRM) - Bo-Chi Zhang; Gui-Rong Zhang; Wei Ji; Rui-Bin Yang; Gui-Wei Zou; Kun-Ci Chen; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics Resources, 2017)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Soil nitrification and foliar δ15N declined with stand age in trembling aspen and jack pine forests in northern Alberta, Canada - Ya-Lin Hu; En-Rong Yan; Woo-Jung Choi; Francis Salifu; Xiao Tan; Z. Chi Chen; De-Hui Zeng; Scott X. Chang (Plant and Soil, 2014)

Toxicity and repellence of Taiwanese indigenous djulis, Chenopodium formosaneum, against Aedes albopictus (Diptera: Culicidae) and Forcipomyia taiwana (Diptera: Ceratopogonidae) - Eddie Hang Chio; En-Cheng Yang; Hsiang-Ting Huang; Err-Lieh Hsu; Chi-Rong Chen; Chin-Gi Huang; Rong-Nan Huang (Journal of Pest Science, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

N-(1-Pyrenyl) maleimide inhibits telomerase activity in a cell free system and induces apoptosis in Jurkat cells - Pei-Rong Huang; Yuan-Ming Yeh; Chia-Chu Pao; Chi-Yuan Chen; Tzu-Chien V. Wang (Molecular Biology Reports, 2012)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

Phylogenetics and Biogeography of the Phalaenopsis violacea (Orchidaceae) Species Complex Based on Nuclear and Plastid DNA - Chi-Chu Tsai; Chiou-Rong Sheue; Chih-Hsiung Chen; Chang-Hung Chou (Journal of Plant Biology, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)